The Impact of Danantara's Establishment on the Indonesian Capital Market (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the reaction of the Indonesian capital market to the establishment of the Danantara Investment Management Agency (BPI) as a new financial institution formed by the government in 2025. Using a quantitative approach through the event study method, this study measures the abnormal return of the Composite Stock Price Index (JCI) around the date of the announcement of Danantara's establishment, namely in the observation period from January 31 to April 17, 2025. The analysis results show that the market reacted significantly negatively on the day of the announcement (t₀) with an abnormal return of -0.78 percent and a p-value of 0.05, while on other days around the event, no significant reaction was found. This indicates that the market responds quickly to public information, but the impact is temporary. In the long term, the cumulative abnormal return (CAR) shows a significant negative trend, reflecting market pressure and investor caution regarding Danantara's existence. These findings are in line with the semi-strong form of market efficiency theory and show that investor confidence is highly dependent on the transparency and governance of state financial institutions. Overall, the results of this study confirm that the establishment of Danantara has not had a sustainable positive impact on the Indonesian capital market.